Gravity, antigravity and gravitational shielding in (2+1) dimensions - Accioly, Antonio Jose [UNESP]; Helayel-Neto, Jose; Lobo, Matheus [UNESP] (Iop Publishing Ltd, 2009)
Higher-derivative terms are introduced into three-dimensional gravity, thereby allowing for a dynamical theory. The resulting system, viewed as a classical field model, is endowed with a novel and peculiar feature: its nonrelativistic potential describes three gravitational regimes. Depending on the choice of the parameters in the action functional, one obtains gravity, antigravity or gravitational shielding. Interesting enough, this potential is very similar, mutatis mutandis, to the potential for the interaction of two superconducting vortices. Furthermore, the gravitational deflection angle of a light ray, unlike that of Einstein gravity in (2+1) dimensions, is dependent on the impact parameter.